Laboratory Room Control Access and Monitoring System Using Fingerprint and XBee Pro S2C - Morlan Pardede; Elferida Hutajulu; Regina Sirait (Jurnal Mantik, 2020)
To able to control the use of laboratory rooms, equipment that can control the access and monitoring the room is needed. This paper describes the room access controller which consist of the fingerprint R307 sensor, LCD, solenoid key, XBee ProS2C, and Arduino Mega 2560. The door room will open if the user has the autorization to open the door’s fingerprints scan. If the door is open then students can register their attendance by scanning their fingerprints. The door will be closed if the authorized user scan his fingerprints again. For each known fingerprint, the microcontroller will send the user ID number to the computer. In the central computer, the list of room users is recorded and saved on a file after the door is closed. With this experiment, the method obtained a tool that can control the access to the laboratory room and can monitor the use of three rooms on the monitoring computer. According to the test results, the tool has been able to control the access and monitor three rooms where the time for fingerprint scanning to be registered on the computer is 2 seconds at the fastest and success rate of scanning a fingerprint is 84.87% on average.